Generation and Characterization of a Dual-Reporter Transgenic Leishmania braziliensis Line Expressing eGFP and Luciferase - Sharma, Rohit; Silveira-Mattos, Paulo S.; Ferreira, Vinicius C.; Rangel, Francys A.; Oliveira, Laíse B.; Celes, Fabiana S.; Viana, Sayonara M.; Wilson, Mary E.; de Oliveira, Camila I. (Frontiers in Cellular and Infection Microbiology, 2020)
In this study, we generated a transgenic strain of Leishmania braziliensis, an etiological agent associated with a diversity of clinical manifestations of leishmaniasis ranging from localized cutaneous to mucocutaneous to disseminated disease. Transgenic parasites expressing reporter proteins are valuable tools for studies of parasite biology, host-pathogen interactions, and anti-parasitic drug development. To this end, we constructed an L. braziliensis line stably expressing the reporters eGFP and luciferase (eGFP-LUC L. braziliensis). The integration cassette co-expressing the two reporters was targeted to the ribosomal locus (SSU) of the parasite genome. Transgenic parasites were characterized for their infectivity and stability both in vitro and in vivo. Parasite maintenance in axenic long-term culture in the absence of selective drugs did not alter expression of the two reporters or infection of BALB/c mice, indicating stability of the integrated cassette. Infectivity of eGFP-LUC, L. braziliensis, both in vivo and in vitro was similar to that obtained with the parental wild type strain. The possibility of L. braziliensis tracking and quantification using fluorescence and luminescence broadens the scope of research involving this neglected species, despite its importance in terms of public health concerning the leishmaniasis burden.